THE INFLUENCE OF RETURN ON ASSETS, RETURN ON EQUITY, EARNING PER SHARE, AND PRICE EARNING RATIO ON STOCK PRICE (A CASE STUDY IN FOOD AND BEVERAGES COMPANIES REGISTERED IN INDONESIA STOCK EXCHANGE) - Banjari, Rasi Akio Dyusuf (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aims to determine the fundamental factors that can affect the company's stock price. Fundamental variables used in this study are Return On Assets (ROA), Return on Equity (ROE), Earning Per Share (EPS) and Price Earning Ratio (PER). The Object of the Research are Food and Beverages companies listed on the Indonesia Stock Exchange (IDX) during the periode of 2010-2014.The population of the study is all Food and Beverages companies listed in Indonesia Stock Exchange (IDX) during the period of 2010-2014. The Samples are selected by purposively, obtaining 15 out of 21 companies listed in IDX. The data analysis involves secondary data which are evaluated through multiple linear regression technique.The result of the analysis shows that ROA, ROE, EPS, and PER Partially give significant influence on stock price. The determination coefficient shows the adjusted R- square value of 0,700%, indicating that 70% of stock price is explainable through the four independent variables of ROA, ROE, EPS and PER. Mean, while the remaining 30% is explained by variables outside the model.Keywords : Stock Price, Return On Assets, Return On Equity, Earning PerÂ Â Share, Price Earning Ratio.